Localization of the autonomic, somatic and sensory neurons innervating the cranial tibial muscle of the pig - Botti, Maddalena; Gazza, Ferdinando; Ragionieri, Luisa; Bo Minelli, Luisa; Panu, Rino (Italian Journal of Anatomy and Embryology, 2011)
The location of sympathetic, somatic and sensory neurons projecting to the cranial tibial muscle of the pig hindlimb was studied with the neuronal non-transynaptic tracer Fast Blue. Additionally, the number and the size of these neurons were determinated. The Fast blue, randomly applied to the cranial tibial muscle belly of 3 pigs, labelled sympathetic neurons in the ipsilateral L5-S3 and contralateral S1 sympathetic trunk ganglia and in the prevertebral caudal mesenteric ganglia of both sides. The somatic motoneurons were identified in the ipsilateral ventral horn of the S1 segment of spinal cord, while the sensory neurons were located in the ipsilateral L7-S1 spinal ganglia. The diameter of the multipolar sympathetic neurons oscillated between 26 and 46 µm in the sympathetic trunk ganglia and between 18 and 42 µm in the caudal mesenteric ganglia. The size of the multipolar spinal motoneurons oscillated between 33 and 102 µm. The size of the pseudounipolar sensory neurons oscillated between 23 and 67 µm. In all ganglia, the labelled neurons were localized at random and did not show a somatotopic distribution. Our results document a conspicuous autonomic innervation projecting to the “classic” skeletal cranial tibial muscle. Probably this innervation is destined to the muscle vessels.